2009
DOI: 10.1016/s1081-1206(10)60162-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elevated exhaled nitric oxide levels on the risk of respiratory tract illness in preschool-aged children with moderate-to-severe intermittent wheezing

Abstract: Background The fractional concentration of exhaled nitric oxide (FeNO) is a noninvasive marker for airway inflammation but requires further study in pre-school children to determine its clinical relevance. Objective To determine whether the risk of respiratory tract illnesses (RTI), disease burden and atopic features are related to FeNO in preschool children with moderate-to-severe intermittent wheezing. Methods We determined FeNO using the off-line tidal breathing technique in 89 children, 12–59 months ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 32 publications
(34 reference statements)
2
20
0
1
Order By: Relevance
“…However, the API, rather than the mAPI, is used to predict asthma in longitudinal studies. 25,26 In most health care settings, it is easier, cheaper, and probably more reliable (allergens vary with region) to determine eosinophilia counts in blood samples than to determine allergic sensitization with a skin prick test or by measuring specific IgEs. The members of the Multicentre Allergy Study performed multiple skin and IgE tests on subjects throughout childhood and used mathematic modeling to show that specific IgE responses did not reflect a single phenotype of atopy; only atopy to multiple factors at early ages predicted asthma at the age of 8 years.…”
Section: Api and Other Indicesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the API, rather than the mAPI, is used to predict asthma in longitudinal studies. 25,26 In most health care settings, it is easier, cheaper, and probably more reliable (allergens vary with region) to determine eosinophilia counts in blood samples than to determine allergic sensitization with a skin prick test or by measuring specific IgEs. The members of the Multicentre Allergy Study performed multiple skin and IgE tests on subjects throughout childhood and used mathematic modeling to show that specific IgE responses did not reflect a single phenotype of atopy; only atopy to multiple factors at early ages predicted asthma at the age of 8 years.…”
Section: Api and Other Indicesmentioning
confidence: 99%
“…32,33 The API is also the only index used in studies to determine relationships between biomarkers, such as comparing fraction of exhaled nitric oxide (FeNO) 25,34 or early lung function (Garcia-Marcos, personal communication). Recently, a prospective cohort study of 391 young children (age, 3-47 months) showed that wheezy young children with a stringent API have increased levels of FeNO compared with those seen in children with recurrent wheeze and a loose API or children with recurrent cough.…”
Section: Applicationsmentioning
confidence: 99%
“…Studies in preschool children have suggested that F eno testing may be a benefi cial tool predicting future asthma. [25][26][27][28][29] Debley et al 26 found F eno level to be predictive of changes in lung function and risk of future wheezing, suggesting a role for prediction of future asthma in infants and toddlers. A large cohort study in The Netherlands also suggested that F eno measured before the age of 4 years was predictive of wheeze up to age 8.…”
Section: Lung Function and Health-care Usementioning
confidence: 99%
“…[26] However, the mean enrollment age was >3 years, and most children < 3yrs. could not perform acceptable tidal breathing FE NO measurements, indicating that unsedated tidalbreathing FE NO may be technically challenging to measure in infants/toddlers.…”
Section: Introductionmentioning
confidence: 99%
“…could not perform acceptable tidal breathing FE NO measurements, indicating that unsedated tidalbreathing FE NO may be technically challenging to measure in infants/toddlers. [26] Additional limitations of tidal breathing-FE NO in infants include: potential nasal NO contamination as nasal NO production far exceeds lower airway production, and variable expiratory flow which is problematic due the highly flow dependent nature of FE NO [27,28].…”
Section: Introductionmentioning
confidence: 99%